PREVENTION OF Helicobacter pylori CAUSING PEPTIC ULCER BY Trigonella foenum graecum - SAHOO, ELINA; TRIPATHY, BIDYASHREE; PANDEY, MUKUNDJEE; BHATTACHARYAY, DIPANKAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Phytochemicals are a powerful group of chemicals that are derived from natural sources, especially from plants. That has shown to exhibit chemoprevention and chemotherapeutic effects not only in cell lines and in animal models of cancer but also some of them are in the clinical trial phase 1and 2.Trigonella foenum graecum plant extract is used to cure peptic ulcer. Alcohol dehydrogenase is used as a key enzyme for it. The strength of the interaction was based on the -CDOCKER energy and -CDOCKER interaction energy.